Overlap Syndrome of Primary Sjögren Syndrome with Antineutrophil Cytoplasmic Antibody (ANCA)-Associated Vasculitis Based on the American College of Rheumatology (ACR)/European Alliance of Associations for Rheumatology (EULAR) Criteria - Hyun Joon Choi; Jang Woo Ha; Jason Jungsik Song; Yong-Beom Park; Sang-Won Lee (Diagnostics)
Background/Objectives: The overlap syndrome of primary Sjögren syndrome (pSS) with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) (OvSD/pSS/AAV) has been reported in other studies. This study applied the new criteria for AAV proposed by the American College of Rheumatology/European Alliance of Associations for Rheumatology in 2022 (the ACR/EULAR criteria) to patients with pSS presenting signs and symptoms suggestive of small- and medium-vessel vasculitis. It also investigated the overall frequency of OvSD/pSS/AAV and the major contributing factors to its reclassification. Methods: This study included 116 patients with pSS from March 2005 to December 2020, according to the inclusion criteria, and defined signs and symptoms suggestive of small- or medium-vessel vasculitides as lung parenchymal lesions supporting AAV, peripheral neuropathy, and suspected renal vasculitis. The classification could be made when the total scores for microscopic polyangiitis (MPA) and granulomatosis with polyangiitis (GPA) are ≥5 points and the eosinophilic GPA (EGPA) score is ≥6 points. Results: The median age of the patients was 56.0 years, and 101 patients (87.1%) were women. In total, 95, 12, and 37 patients had lung parenchymal lesions supporting AAV, peripheral neuropathy, and suspected renal vasculitis, respectively. According to the ACR/EULAR criteria for AAV, 35 of 116 (30.2%) patients were reclassified as having OvSD/pSS/AAV. Among these 35 patients, 4 were reclassified as having both OvSD/pSS/MPA and OvSD/pSS/GPA and 1 as having both OvSD/pSS/MPA and OvSD/pSS/EGPA simultaneously. The major contributing factor to the reclassification of OvSD/pSS/AAV was ANCA positivity. Conclusions: The overall frequency of the reclassification of OvSD/pSS/AAV was 30.2% in pSS patients presenting signs and symptoms suggestive of small- and medium-vessel vasculitis. Its likelihood increased according to ANCA positivity.